2021
DOI: 10.1136/bmjophth-2021-000709
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden and loss of quality of life from dry eye disease in Canada

Abstract: ObjectiveTo describe the direct and indirect cost estimates of dry eye disease (DED), stratified by disease severity, and the impact of DED on quality of life (QoL) in Canadian patients.Methods and analysisA prospective, multicentre, observational, cross-sectional study was conducted at six sites across Canada. Eligible patients completed a 20 min survey on demography, general health, disease severity, QoL and direct (resource utilisation and out-of-pocket expenses for the past 3–24 months) and indirect costs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…The available literature suggests that DED carries high socioeconomic costs as a result of both direct medical costs (health care visits and prescribed/over-the-counter drugs) and indirect costs (from impaired productivity or work absenteeism). 32 , 41 In the US, the annual burden of DED on the health care system has been estimated to be $3.84 billion. Lost work days and reduced productivity add another $55.4 billion in indirect costs.…”
Section: Discussionmentioning
confidence: 99%
“…The available literature suggests that DED carries high socioeconomic costs as a result of both direct medical costs (health care visits and prescribed/over-the-counter drugs) and indirect costs (from impaired productivity or work absenteeism). 32 , 41 In the US, the annual burden of DED on the health care system has been estimated to be $3.84 billion. Lost work days and reduced productivity add another $55.4 billion in indirect costs.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that ergonomic measures while desk working in an office affect workers’ pain symptoms and performance 14,15 . Previous studies have shown that brightness and temperature/humidity factors may cause visual display terminal (VDT) syndrome among office workers, with eye strain and low back pain being consequences of the effects of the visual environment and working posture 16,17 . Similar effects are considered to occur in WFH.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Previous studies have shown that brightness and temperature/humidity factors may cause visual display terminal (VDT) syndrome among office workers, with eye strain and low back pain being consequences of the effects of the visual environment and working posture. 16,17 Similar effects are considered to occur in WFH. Foot space and working at an inappropriate table also may lead to inadequate postural adjustments and lower back pain.…”
Section: Discussionmentioning
confidence: 99%
“…The Tear Film and Ocular Surface Society (TFOS) defined dry eye as “a multifactorial disease of the ocular surface characterized by a loss of homeostasis of the tear film, and accompanied by ocular symptoms, in which tear film instability and hyperosmolarity, ocular surface inflammation and damage, and neurosensory abnormalities play etiological roles.” 282 It is a disease of both symptoms and signs, so it is a subset of ocular surface disease. It was acknowledged as a disease, rather than a condition, because of its impact on individuals' lives, impacting quality of life, livelihoods, 283–285 and mental health 286–288 . Its prevalence has been reported to vary widely across different populations, 289 but some of the variation is likely due to the previous lack of accepted diagnostic criteria.…”
Section: Technology-driven Enhancements In Ocular Surface Disease Dia...mentioning
confidence: 99%